2011
DOI: 10.1061/(asce)ir.1943-4774.0000373
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Identifying the Best Equations for Estimating the Time of Concentration of Watersheds in a Particular Region

Abstract: In this paper, a methodology is proposed for identifying the best equations for estimating the time of concentration (ToC) of watersheds located in a specific geographic region. The methodology primarily works on the basis of modifying available equations to minimize their bias for any particular region of interest. In the methodology, for each watershed, the ToC considered as "reference" is determined using the Natural Resource Conservation Service (NRCS) velocity method employed in the TR-55 model and geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 10 publications
0
40
0
7
Order By: Relevance
“…It is one of the most critical parameters for any hydrological analysis and the subsequent design of a hydraulic structure aimed at managing stormwater. Many methodologies (empirical and semi-empirical) have been proposed for its estimation [24,25]. For this study, the Kirpich method was used (Equation (6)) [26], as the Gordo creek watershed fits some of the morphometric characteristics needed for using this formula [25].…”
Section: Time Of Concentration Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is one of the most critical parameters for any hydrological analysis and the subsequent design of a hydraulic structure aimed at managing stormwater. Many methodologies (empirical and semi-empirical) have been proposed for its estimation [24,25]. For this study, the Kirpich method was used (Equation (6)) [26], as the Gordo creek watershed fits some of the morphometric characteristics needed for using this formula [25].…”
Section: Time Of Concentration Estimationmentioning
confidence: 99%
“…The goodness-of-fit test of Akaike Information Criterion (AIC), with values of 753.3721 and 747.5103 for stationary and non-stationary conditions respectively, showed that the latter best depicts the increasing rainfall pattern. Values of rainfall were later estimated for different return periods (2,5,10,25, 50, and 100 years) to quantify the increase (non-stationary versus stationary condition), which ranged 6% to 12% for return periods from 5 years to 100 years, and 44% for a 2-year return period. The effect of these findings were tested in the Gordo creek watershed by first calculating the resulting direct surface runoff (DSR) for various return periods, and then modeling the hydraulic behavior of the downstream area (composed of a 178.5-m creek's reach and an existing box-culvert located at the watershed outlet) that undergoes flooding events every year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, T c was equal to 3.28 h regarding the Giandotti's formula, whereas it was equal to 1.79 h with respect to the Kirpich's equation. Adjustment factors are superposed by many scientists thus far, in order to bias correct the estimations of T c , due to application of the aforementioned empirical formulas to catchments of different location and geomorphology of the ones originally fitted [42][43][44]. A correction factor of 2.0 may be applied to general overland flow and natural grass channels, whereas a correction factor of 1.0 can be adjusted to overland flow on bare soil or roadside ditches [32].…”
Section: Simulation Of the Precipitation Event Of 17 October 2006 Usimentioning
confidence: 99%
“…Not having observed runoff data at the catchment's outlet, we could not use statistical indices such as Nash-Sutcliffe to calibrate the model. Instead, we collected the most considerable runs (42) in order to better approach the aforementioned calibration and validation criterion. We believe that with the method followed, we approached quite sufficiently the range of uncertainty of the resulted hydrograph.…”
Section: Calibration Of the Hydrological Modeling And Parameter Sensimentioning
confidence: 99%